Stabilometric assessment of static balance and postural stability in multicanal vertigo post vestibular rehabilitation: a clinical case report (Research, Society and Development, 2021)
Introduction: Multicanal vertigo is a rare disorder and vestibular rehabilitation is one of the treatment methods, aiming to stimulate the neuroplasticity of the central nervous system. Objective: To examine the effect of a vestibular rehabilitation program on static balance and postural stability in an individual with vertigo. Case report: Male patient, 58 years old, with clinical diagnosis of benign paroxysmal positional vertigo for 12 years, with frequent episodes of vertigo, loss of balance and falls. The assessment of balance and postural stability were performed using the Romberg test with eyes open and closed, on a S-Plate v.14 – Medicapteurs – France, force platform, analysing data at a risk of p